2016
DOI: 10.1002/ejoc.201600005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis, Photophysical Properties, and X‐ray Structures of N‐Heteroacenes

Abstract: Abstract:The described mechanochemical methodology is an example of a proof-of-concept in which solution-based tedious, poor yielding, and difficult syntheses of pyrazaacenes are achieved under solvent-free ball-milling conditions; the method is easy, high yielding, time-efficient, and environmentally benign. The synthesized compounds also include pyrazaacenes (N-heteroacenes) that are octacene analogues containing pyrene building blocks. The compounds were sparingly soluble in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 72 publications
3
35
0
Order By: Relevance
“…The large CT nature of the excited state becomes more evident when comparing the emission of 8 with previously reported analogues that only possess a donor or acceptor moiety. Derivative VIII emits in the blue region with λ max (em)=471 nm and compound IV (unfortunately, there is no report of an emission of compound III ) emits in the green region with λ max (em)=520 nm (both in CH 2 Cl 2 ) while we observe a λ max (em)=700 nm for 8 in CH 2 Cl 2 . Nevertheless, the non‐radiative decay rates are significantly increased in CH 2 Cl 2 ( k nr =11×10 7 s −1 ), which is fully in line with the energy gap law as the reorganization energy is enhanced in polar solvents .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The large CT nature of the excited state becomes more evident when comparing the emission of 8 with previously reported analogues that only possess a donor or acceptor moiety. Derivative VIII emits in the blue region with λ max (em)=471 nm and compound IV (unfortunately, there is no report of an emission of compound III ) emits in the green region with λ max (em)=520 nm (both in CH 2 Cl 2 ) while we observe a λ max (em)=700 nm for 8 in CH 2 Cl 2 . Nevertheless, the non‐radiative decay rates are significantly increased in CH 2 Cl 2 ( k nr =11×10 7 s −1 ), which is fully in line with the energy gap law as the reorganization energy is enhanced in polar solvents .…”
Section: Resultssupporting
confidence: 83%
“…Derivative VIII emits in the blue region with l max (em) = 471 nm and compound IV (unfortunately, there is no report of an emission of compound III) emits in the green region with l max (em) = 520 nm (both in CH 2 Cl 2 ) while we observe a l max (em) = 700 nm for 8 in CH 2 Cl 2 . [32,46] Nevertheless, the non-radiative decay rates are significantly increased in CH 2 Cl 2 (k nr = 11 10 7 s À1 ), which is fully in line with the energy gap law as the reorganization energy is enhanced in polar solvents. [61] Therefore, the quantum yield is strongly decreased in the polar solvent.…”
Section: Photophysical and Redox Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…It was found that many reactions occur much faster as in solution, they can be performed under milder conditions, and the product is isolated in higher yields, compared to the corresponding reaction in solution. [17] Similar process improvements under mechanochemical conditions were achieved for a variety of reactions, for example the amidation of aldehydes, [18] the fluorination of 1,3-diketones, [19] the Michael addition, [20,21] the Knoevenagel condensation, [22] and the Morita-Baylis-Hillman reaction. The reactions were over in 4 h, yielding the products in very good to excellent yield (76-95 %).…”
Section: Mechanochemistry In Organic Synthesismentioning
confidence: 73%
“…A couple of mechanochemical methods for the construction of quinoxaline ring are available in literature . Sahoo et al reported a method for the synthesis of quinoxaline based heteroacences using a ball‐mill . On the other hand, a hand‐grinding method by Li et al is also available in which basic Al 2 O 3 was used as reaction media and products were purified by column chromatography.…”
Section: Introductionmentioning
confidence: 99%